Study of silicon photomultipliers for use in neutron decay experiments - Dubbers, Dirk (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
Photon readout of plastic scintillators is investigated with the aim of improving the precision of neutron β decay experiments. Neutron decay is nowadays studied with high statistics, based on up to 109 registered decay events, and leads to strongly improved limits on new physics beyond the standard model, with βs often registered in plastic scintillators. The main systematic errors in these experiments are due to imperfect characterization of the scintillators with respect to linearity, energy resolution, and electron backscattering. We study whether these errors can be diminished when the conventional photomultipliers used for scintillator readout are replaced by silicon photomultipliers (SiPMs). To this end, various theoretical and experimental tools are developed, and a procedure for handling the extreme dark rates of SiPMs is proposed. In β spectroscopy, so the conclusion, plastic scintillator readout with SiPMs can significantly improve energy response, and help providing reliable corrections for electron backscattering.
Gesehen am 09.07.2021